2006
DOI: 10.1002/jts.20165
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of an Internet traumatic stress survey with a college student sample

Abstract: The reliability and validity of Internet-based questionnaires were assessed in a sample of undergraduates (N = 411) by comparing data collected via the Internet with data collected in a more traditional format. A 2 x 2 x 2 repeated measures factorial design was used, forming four groups: Paper-Paper, Paper-Internet, Internet-Paper, and Internet-Internet. Scores on measures of trauma exposure, depression, and posttraumatic stress symptoms formed the dependent variables. Statistical analyses demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Further support for this method of data collection comes from research suggesting that Internet-based trauma surveys are highly correlated with both paper-and-pencil and interview methods, regardless of level of symptomatology (Read, Farrow, Jaanimägi, & Ouimette, 2009), and demonstrate similar psychometric properties (Fortson, Scotti, Del Ben, & Chen, 2006). Moreover, prior focus group recommendations regarding effective trauma research with a Japanese population encouraged utilizing a more anonymous method of disclosure, such as the Internet (Allard, 2009), in light of AV that may hinder disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for this method of data collection comes from research suggesting that Internet-based trauma surveys are highly correlated with both paper-and-pencil and interview methods, regardless of level of symptomatology (Read, Farrow, Jaanimägi, & Ouimette, 2009), and demonstrate similar psychometric properties (Fortson, Scotti, Del Ben, & Chen, 2006). Moreover, prior focus group recommendations regarding effective trauma research with a Japanese population encouraged utilizing a more anonymous method of disclosure, such as the Internet (Allard, 2009), in light of AV that may hinder disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…From a demographical point of view, there were no differences between the questionnaires that were ruled out and those that were finally analyzed. Despite the self-selection bias that this type of procedure may exhibit, its correct use together with individualized screening filters has been widely accepted as an adequate and valid contemporaneous sampling method (Eiroá-Orosa, Fernández-Pinto, & Pérez-Sales, 2008;Fortson, Scotti, del Ben, & Chen, 2006). Our online questionnaire followed the technical recommendations provided by the main web-based studies available to date (Dillman, 2007).…”
Section: Methods Samples and Recruitment Proceduresmentioning
confidence: 99%
“…One of the major concerns raised by researchers is that the responses on PP surveys will differ from the responses on online surveys because the anonymity of the Internet might lead to disinhibition (Fortson et al, 2006;Joinson, 1999). This would be a particular concern for SWB data collected over the Internet because of the sensitive nature of SWB and the need to assess typical emotional states to form constructs of SWB.…”
mentioning
confidence: 99%
“…The results were the exact opposite: Employees who were higher in self-monitoring reported less job satisfaction on the PP survey. Finally, Fortson et al (2006) showed that although the reporting of traumatic events cal conditions under which Internet surveys are completed are uncontrolled and are unknown to the researchers. Bech and Kristensen (2009) noted that although online surveys may have cost, time, and effort advantages over PP surveys, online surveys with lower response rates are prone to a nonresponse bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation